Implementation of the Needs Assessment Tool for patients with interstitial lung disease (NAT:ILD): facilitators and barriers. Issue 11 (20th February 2017) - Reigada, C; Papadopoulos, A; Boland, J W; Yorke, J; Ross, J; Currow, D C; Hart, S; Bajwah, S; Grande, G; Wells, A; Johnson, M J
Abstract : A Needs Assessment Tool (NAT) was developed previously to help clinicians identify the supportive/palliative needs of people with interstitial lung disease (ILD) (NAT:ILD). This letter presents barriers and facilitators to clinical implementation. Data from (1) a focus group of respiratory clinicians and (2) an expert consensus group (respiratory and palliative clinicians, academics, patients, carers) were analysed using Framework Analysis. Barriers related to resources and service reconfiguration, and facilitators to clinical need, structure, objectiveness, flexibility and benefits of an 'aide-memoire'. Identified training needs included communication skills and local service knowledge. The NAT:ILD was seen as useful, necessary and practical in everyday practice.